2011
DOI: 10.3892/or.2011.1352
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide re-sensitizes ERα-negative breast cancer cells to endocrine therapy by restoring ERα expression in vitro and in vivo

Abstract: Abstract. Approximately one-third of breast cancers lack estrogen receptor α (ERα) because of the hypermethylation of the CpG island in the receptor's promoter. These tumors are associated with poorer histological differentiation, a higher growth fraction, are rarely responsive to endocrine therapy and have a worse clinical outcome. Thus, re-expression of ERα in ERα-negative breast cancers may restore the sensitivity of antiestrogen therapy. The ERα-negative breast cancer cell line MDA-MB-435s was treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Arsenic was also active in the steroid synthesis and estrogenic activity assays, which could indicate that a ) other biological activity of arsenic limits its activity in the mammary gland, such as the differential induction of cell death in breast cancer cells ( Ruiz-Ramos et al 2009 ), or b ) further epidemiologic study might detect an association between arsenic and breast cancer. Interestingly, arsenic has been investigated as a clinical treatment for advanced breast cancer ( Liu et al 2012 ; Zhang et al 2011 ), and a negative association has recently been observed between exposure to elevated arsenic levels in drinking water and breast cancer mortality in Chile ( Smith et al 2014 ). Caprolactam emerged from the pilot test without any indications of genotoxicity, but there is no human evidence, and scant data on endocrine disruption or cancer hallmarks.…”
Section: Resultsmentioning
confidence: 99%
“…Arsenic was also active in the steroid synthesis and estrogenic activity assays, which could indicate that a ) other biological activity of arsenic limits its activity in the mammary gland, such as the differential induction of cell death in breast cancer cells ( Ruiz-Ramos et al 2009 ), or b ) further epidemiologic study might detect an association between arsenic and breast cancer. Interestingly, arsenic has been investigated as a clinical treatment for advanced breast cancer ( Liu et al 2012 ; Zhang et al 2011 ), and a negative association has recently been observed between exposure to elevated arsenic levels in drinking water and breast cancer mortality in Chile ( Smith et al 2014 ). Caprolactam emerged from the pilot test without any indications of genotoxicity, but there is no human evidence, and scant data on endocrine disruption or cancer hallmarks.…”
Section: Resultsmentioning
confidence: 99%
“…Arsenic trioxide could suppress cancers of the liver, prostate, and esophagus through demethylation or, for example, by induction of apoptosis. Zhang et al recently showed that arsenic trioxide induces re-expression of ER in MDA-MB-435s and also inhibits tumour growth in mice [22]. However, there is evidence that MDA-MB-435 cell line is not actually from a breast cancer lineage, but in fact are derived from a melanoma cell line, M14 [23].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to irreversible genetic mutations, epigenetic changes such as occur in the ERα gene are potentially reversible (34) making these changes amenable to pharmacological interventions (35). Currently there are no agents that achieve re-expression of ERα in the clinic although certain HDAC inhibitors, demethylating agents, epigallocatechin-3-gallate (a major polyphenol in green tea) and arsenic trioxide have been shown to re-express ERα in experimental models (36,37). Src expression and activity is inversely correlated with ERα levels in human primary breast cancers (15,38,39) suggesting that Src kinase inhibition may be a strategy for re-expression of ERα and restoration of sensitivity to endocrine therapies.…”
Section: Discussionmentioning
confidence: 99%